THE FORMATION OF SPEAKING SKILLS THROUGH THE METHODS OF COMMUNICATION (Ta'limning zamonaviy transformatsiyasi, 2024)
ANNOTATION: The article discusses the importance of developing and improving speaking skills in teaching English. The authors examine both subjective and objective factors that influence the success of mastering speaking proficiency. Additionally, various authors' positions on methods and approaches aimed at developing speaking skills are analyzed. Some difficulties encountered in mastering speaking skills in English language classes are addressed. The authors emphasize the priority of the communicative competencies of both teachers and students in teaching English. During the analysis of scientific works dedicated to the problem of developing speaking skills, the author formed their views on the main difficulties in developing speaking abilities and identified the causes behind them. The article also highlights the significance of teachers' knowledge level when preparing practical tasks for speaking activities, as well as their ability to actively utilize their psychological and pedagogical competencies in practice.